The effects of nebivolol therapy on QT dispersion in patients with congestive heart failure - Karadag, Makbule Kutlu; Akbulut, Mehmet; Yilmaz, Özbay (My University, 2008)
Nebivolol results in a significant improvement in Left Ventricular (LV) systolic function and prognosis in patients with Congestive Heart Failure (CHF) but it is unknown whether nebivolol effects QT dispersion (QTd), which is related with sudden cardiac death. Aim of this study was to investigate the effects of nebivolol on QTd in heart failure patients. Fifty CHF patients (age 65±11 years, 31 male) with a LV ejection fraction ?35% and in New York Heart Association (NYRA) class II-III were included in this study. After the 1 month standard heart failure therapy; nebivolol was added on standard therapy at an initial dose of 2.5 mg and up titrated to the maximum tolerated dose. At baseline and at the 3rd month of nebivolol treatment all patients were assessed by clinical, laboratory, electrocardiographic and echocardiographic examinations. From 12-lead standard ECG maximum and minimum QT intervals (QTmax, QTmin), QTd, corrected QT intervals (QTcmax, QTcmin) and corrected QTd (QTcd) values were calculated at baseline and at the end of follow-up period. Mean nebivolol dose was 4.5±0.49 mg. QTd and QTcd values significantly decreased with nebivolol therapy (QTd: 81±25 vs. 71±22 ms, p<0.0001; QTcd: 86±27 vs 70±16 ms, p<0.0001. While QTcmax decreased significantly (p<0.001), there was no statistically significant changes in QTcmin value. A significant reduction was noted in the resting heart rate (94±26 vs 75±12 bpm, p<0.0001), systolic and diastolic bloodpressures (p<0.0001). Left ventricular systolic functions also had significant improvement that Ejection Fraction (EF) increased from 28.8±3.4-31.4±4%, (p<0.0001). As a conclusion, added-on nebivolol therapy for 3 months was associated with a significant decrease in QTd and QTcd values and improvement in systolic functions in heart failure patients. This effect of nebivolol, which is due to the improvement in myocardial repolarization properties and special vasodilatory effects, may contribute to a possible reduction in sudden cardiac death in congestive heart failure patients. © Medwell Journals, 2008.
Keywords: Congestive; Heart failure; Left ventricular; Nebivolol; Patient; QT dispersion